Failing to get the gist of what's being said: background noise impairs higher-order cognitive processing - Marsh, John E.; Ljung, Robert; Nöstl, Anatole; Threadgold, Emma; Campbell, Tom A. (Frontiers in Psychology, 2015)
A dynamic interplay is known to exist between auditory processing and human cognition. For example, prior investigations of speech-in-noise have revealed there is more to learning than just listening: Even if all words within a spoken list correctly heard in noise, later memory for those words is typically impoverished. At such low signal-to-noise ratios when listeners could identify words, those participants could not necessarily remember those words. These investigations supported a view that there is a “gap” between the intelligibility of speech and memory for that speech. Here, the notion was that this gap between speech intelligibility and memorability is a function of the extent to which the spoken message seizes limited immediate memory resources (e.g., Kjellberg, Ljung, & Hallman, 2008). Accordingly, the more difficult the processing of the spoken message, the less resources are available for elaboration, storage, and recall of that spoken material. However, it was not previously known how increasing that difficulty affected the memory processing of semantically rich spoken material. This investigation showed that noise impairs higher levels of cognitive analysis. A variant of the Deese-Roediger-McDermott procedure that encourages semantic elaborative processes was deployed. On each trial, participants listened to a 36-item list comprising 12 words blocked by each of 3 different themes. Each of those 12 words (e.g., bed, tired, snore…) was associated with a “critical” lure theme word that was not presented (e.g., sleep). Word lists were either presented without noise or at a signal-to-noise ratio of 5 decibels upon an A-weighting. Noise reduced false recall of the critical words, and decreased the semantic clustering of recall. Theoretical and practical implications are discussed.